2002
DOI: 10.1385/bter:89:1:43
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Factors on Calcium Bioavailability

Abstract: There are several factors that affected calcium bioavailability, such as physiological and dietary factors. These dietary factors help to achieve an appropiate status of calcium for a correct bone mineralization. In this pathway, recently some compounds present in milk that seem improve calcium absorption such as lactose and certain caseinophosphopeptides formed during digestion of caseins have been studied. On the other hand, the possible inhibitatory effect of fiber has been also studied, without conclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The fibre content of duplicate meals did not influence the dialysable Ca fraction and Ca dialysabilities, a finding that agrees with that pointed out by others [3,38]. Others stated that the possible inhibitatory effect of fibre on Ca bioavailability showed nonconclusive results between in vitro and in vivo studies [38,39]. On the other hand, other researchers [20,22] found that dietary fibre had a negative effect on Ca dialysability.…”
Section: Total and Dialysable Ca Fractions And Corresponding Ca Dialysupporting
confidence: 85%
“…The fibre content of duplicate meals did not influence the dialysable Ca fraction and Ca dialysabilities, a finding that agrees with that pointed out by others [3,38]. Others stated that the possible inhibitatory effect of fibre on Ca bioavailability showed nonconclusive results between in vitro and in vivo studies [38,39]. On the other hand, other researchers [20,22] found that dietary fibre had a negative effect on Ca dialysability.…”
Section: Total and Dialysable Ca Fractions And Corresponding Ca Dialysupporting
confidence: 85%
“…The AWP fraction is comprised of highly phosphorylated proteins and peptides, some of which are derived from caseins (Reid et al, 2004). Phosphorylated casein peptides have been shown to improve calcium absorption by binding to calcium and maintaining the cation in a soluble form (Camara-Marton & AmaroLopez, 2002;Tsuchita, Goto, Yonehara, & Kowata, 1995).…”
Section: Article In Pressmentioning
confidence: 99%
“…Intestinal Ca 2ϩ absorption may depend, not only on dietary Ca 2ϩ and serum vitamin D concentrations, but also on dietary factors that may alter luminal Ca 2ϩ concentrations or interfere with Ca 2ϩ transporters. Dietary factors that have been shown to affect Ca 2ϩ bioavailability include plant fiber, fat, phosphorus, protein, and carbohydrate (1,2,9,35). Concerning potential interactions between intestinal carbohydrate and Ca 2ϩ absorption, most investigations have focused on the stimulating effect of the milk sugar lactose on the absorption of Ca 2ϩ (3,14,27,51,52), as these two nutrients are typically in the intestinal lumen at the same time.…”
mentioning
confidence: 99%